Growth of Artificial intelligence (AI) in Agriculture - Singh, Bhavya (Indian Farming, 2018)
Digitalization has immense scope to transform the agricultural sector. It assumes importance as feeding the entire population is a challenge facing us. With the help of artificial intelligence, farmers are now able to grow better crops and look after their animals while saving time and energy. The combination of artificial intelligence and big data will move this industry towards digitalization. But our farmers’ awareness of artificial intelligence was found to be almost nil. Only few farmers were found to have read about artificial intelligence aspects like drones and robotics etc or browsed online. It implies need to generate awareness and create infrastructure to meet this imperative technological need to revamp Indian agricultural sector.